Anatomy, classification of intersinus septal cell and its clinical significance in frontal sinus endoscopic surgery in Chinese subjects - Wang, Min; Yuan, Fei; Qi, Wei-wei; Cheng, Jye-yuan; Yuan, Xiao-pei; Han, Lin; Xing, Zhi-min (Chinese medical journal, 2012)
Background Intersinus septal cell （ISSC） is not a very uncommon frontal recess cell. But it is poorly described in literature. The clinical significance of this anatomic variant still remains unclear. The purpose of this study was to clarify the anatomy, classification of ISSC and its clinical significance in Chinese subjects. Methods We prospectively identified ISSC in 200 consecutive subjects who had undergone computed tomography （CT） scans： 120 without frontal sinusitis （group 1 ） and 80 with frontal sinusitis （group 2）. The ISSC was classified into two types： Type ⅠISSC communicated with frontal sinuses, type Ⅱ ISSC communicated with frontal recess. The patients of frontal sinusitis had undergone functional endoscopic sinus surgery with the assistance of the classification of ISSC. Statistical analysis was performed to correlate the ISSC and its type to the presence of frontal sinusitis. Results The ISSC was obvious when reviewing the coronal and axial CT scans. Of the 200 CT scans reviewed, ISSC were present in 90 （45%）. Of the 120 scans in group 1, ISSC were present in 49 （41%）, among which type ⅠISSC was in 22 （18%） and type Ⅱ was in 27 （23%）. Of the 80 scans in group 2, ISSC was present in 41 （51%）, among which type Ⅰ ISSC was in 16 （20%） and typeⅡwas in 25 （31%）. There were no statistically significant differences about the frequency distribution of total ISSC, type Ⅰ and Ⅱ ISSC between group 1 and group 2. Conclusions The prevalence of ISSC was very high in Chinese patients. The classification of ISSC was helpful for surgeon to operate according to whether it communicated with frontal sinus or frontal recess. The type Ⅱ ISSC could be relatively easily removed from frontal recess.